Patient characteristics and treatment patterns for patients with benign prostatic hyperplasia, erectile dysfunction or co‐occurring benign prostatic hyperplasia and erectile dysfunction in general practices in the UK: a retrospective observational study. Issue 8 (25th May 2015) - Ilo, D.; Raluy‐Callado, M.; Graham‐Clarke, P.; Sadasivan, R.; Birt, J.; Donaldson, R.; Zhu, E.; Kirby, M. G.; Neasham, D.
Summary Aims The aim of this study was to assess patient characteristics, medication treatment patterns and healthcare resource utilization among men with existing erectile dysfunction (ED) or benign prostatic hyperplasia (BPH), who are newly diagnosed with the second condition (BPH or ED) compared with those with only one condition. Methods This retrospective cohort study utilized the Clinical Practice Research Datalink. Males, aged 40 years or older, newly diagnosed with ED or symptomatic BPH between 1 June 2010 and 31 May 2011, were selected. Patient demographics, existing comorbidities and baseline medication use were analysed. Treatments initiated for the incident condition and treatment patterns were reported at 6, 12, 18 and 24‐months postdiagnosis. Referrals to urologists and visits to general practitioners were reported around diagnosis and during follow‐up. Results This study included 11, 501 incident patients with BPH, of which 23% had a prior ED diagnosis and 9, 734 incident patients with ED, of which 17% had a prior BPH diagnosis. The average age at diagnosis of BPH was similar across both cohorts. Among incident patients with ED, those with prior diagnosis of BPH were diagnosed at an older average age (65 ± 9.2 years) compared to those without BPH (57 ± 9.1 years). The majority of patients in both incident BPH cohorts (62.9–65.5%) were prescribed alpha‐blockers as initial treatment. The majority of patients in both incident ED cohorts (49.6–51.6%) were prescribed sildenafil as initial treatment followed by tadalafil (24.3–26.0%). At 12 months, 50% of incident patients with BPH and 80% of patients with ED had discontinued the therapy initiated. Conclusion This study found that in the UK, patients with co‐occurring BPH and ED when newly diagnosed with the second condition initiated the same treatments as those without prior ED or BPH. During the first year, treatment patterns including discontinuation were comparable in the groups with one of the conditions and co‐occurring BPH and ED.